Primary composition and pigments of 11 red seaweed species from the Center of Portugal - Freitas, Marta (2022)
Macroalgae have been regarded as a natural food source since ancient times, their nutritional value being not only proven by recent studies, but also triggering further in-depth research efforts on the matter. The present study aims to provide an insight into the nutritional potential of selected red seaweed species collected in central Portugal by specifically comparing the moist yield and ash content, crude protein, total lipids, carbohydrates and pigment content between species and, ultimately, finding out if there are differences between taxa. The results obtained highlighted the most nutritionally appealing species, namely, Plocamium cartilagineum with respect to protein content (23.18% dw) and Sphaerocococcus coronopifolius with respect to carbohydrate content (40.23% dw), while none of the species studied showed a lipid content higher than 1.80% dw. Regarding pigment content, the highest concentrations of phycoerythrin, carotenoid and chlorophyll a were obtained, respectively, from P. cartilagineum (0.09 mg.mL−1), Porphyra umbilicalis (1.88 µg.g−1 fw) and Jania rubens (38.41 µg.mL−1). We concluded that there are significant differences between the species studied regarding their nutritional profile, with a marked difference between Corallinales and all other species not belonging to this order; regarding pigment content, this variation between orders was not observed. Nevertheless, all the studied species may act as promising complements in a human healthy diet.